Toxicity and Bioremediation of Heavy Metals Contaminated Ecosystem from Tannery Wastewater: A Review - Bernard E. Igiri; Stanley I. R. Okoduwa; Grace O. Idoko; Ebere P. Akabuogu; Abraham O. Adeyi; Ibe K. Ejiogu (Journal of Toxicology)
The discharge of untreated tannery wastewater containing biotoxic substances of heavy metals in the ecosystem is one of the most important environmental and health challenges in our society. Hence, there is a growing need for the development of novel, efficient, eco-friendly, and cost-effective approach for the remediation of inorganic metals (Cr, Hg, Cd, and Pb) released into the environment and to safeguard the ecosystem. In this regard, recent advances in microbes-base heavy metal have propelled bioremediation as a prospective alternative to conventional techniques. Heavy metals are nonbiodegradable and could be toxic to microbes. Several microorganisms have evolved to develop detoxification mechanisms to counter the toxic effects of these inorganic metals. This present review offers a critical evaluation of bioremediation capacity of microorganisms, especially in the context of environmental protection. Furthermore, this article discussed the biosorption capacity with respect to the use of bacteria, fungi, biofilm, algae, genetically engineered microbes, and immobilized microbial cell for the removal of heavy metals. The use of biofilm has showed synergetic effects with many fold increase in the removal of heavy metals as sustainable environmental technology in the near future.